2012
DOI: 10.3109/08982104.2012.742537
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal formulations of poorly soluble camptothecin: drug retention and biodistribution

Abstract: Context: Camptothecin (CPT) represents a potent anticancer drug. Its therapeutic use however is impaired by both drug solubility, hydrolysis and protein interactions in vivo. Use of liposomes as drug formulation approach could overcome some of these challenges.Objective: The objective of this study was to perform a mechanistic study of the incorporation and retention of the lipophilic parent CPT-compound in different liposome formulations using radiolabeled CPT and thus be able to identify promising CPT delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 71 publications
0
19
0
2
Order By: Relevance
“…It is well established that the size distribution of nanoparticles is a major determinant of their biodistribution and serum stability as well as antitumor activities . Herein, we firstly assessed the size distribution of our liposome after successful fabrication, the results of which are shown in Figure A and Table .…”
Section: Resultsmentioning
confidence: 99%
“…It is well established that the size distribution of nanoparticles is a major determinant of their biodistribution and serum stability as well as antitumor activities . Herein, we firstly assessed the size distribution of our liposome after successful fabrication, the results of which are shown in Figure A and Table .…”
Section: Resultsmentioning
confidence: 99%
“…Liposomes, artificially spherical vesicles prepared from naturally derived phospholipids, are widely known as the versatile biomedical materials of choice for the successful delivery of poorly water‐soluble anticancer drugs (PWSADs) 1–5 . Comprising at least one lipid bilayer enclosed aqueous core, liposomes have several advantages for delivery of PWSADs, such as enhancing drug solubility, serving as a sustained release system, reducing the toxic effect of drugs and providing protection against drug degradation 6–8 .…”
Section: Introductionmentioning
confidence: 99%
“…Among packaging materials for drug delivery, liposome has several advantages, for example, a similar structure to the cell membrane which grants them good biocompatibility, a large surface area, and lack of cytotoxicity 21, etc. Several studies have demonstrated that engineering of liposomes with systematically varied properties by multiple ligands, could thereby improve their in vivo functions 22, 23.…”
Section: Introductionmentioning
confidence: 99%